URGENCY OF REFORMING THE SOCIAL SECURITY ORGANIZING BODY IN THE WELFARE STATE FRAMEWORK - Roziqin Roziqin (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2020)
To realize social security, especially in the health sector, Indonesia established Law Number 40 of 2004 concerning the National Social Security System (SJSN) and Law Number 24 of 2011 concerning the Social Security Organizing Body (BPJS). Law Number 24 of 2011 targeted all Indonesian citizens to become BPJS participants in 2019, including even foreign nationals who have lived for more than six months. However, BPJS, as a public legal entity, has not yet shown excellent performance, as indicated by its deficit every year. This study uses a qualitative approach that is descriptive normative, to explain the concept of the welfare state in the National Social Security System in Indonesia, the implementation of the welfare state in the management of BPJS Healthcare in Indonesia, as well as the reforms needed for the BPJS. This study shows that the Indonesian government has an extensive role in implementing the welfare state concept in the Social Security System by forming BPJS. That significant role is starting from the formulation, management, to the accountability of the BPJS Healthcare. However, the implementation of the welfare state has not been put in proper way by the BPJS Healthcare, so that the government needs to reform the BPJS Healthcare.